2020
DOI: 10.3746/pnf.2020.25.3.286
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Hydroxypropylated Apios Starches

Abstract: Apios ( Apios americana Medikus), also called the potato bean, Indian potato, or groundnut, belongs to the legume family, and is widely distributed across eastern North America. Apios starch was hydroxypropylated, and its physicochemical and structural characteristics were investigated in this study. The starch was extracted by alkali precipitation method, and hydroxypropylated apios starch (HPAS) was prepared using propylene oxide at concentrations of 2.5, 5, 7.5, and 10% (v/w). X-ray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Mehboob et al (2021) also found an increase in the water holding capacity of sorghum starch due to the introduction of hydroxypropyl groups into the starch structure. Increased water uptake percentage of different starches due to the hydroxypropylation process has been reported by different researchers (Karim et al, 2008;Park & Kim, 2020;Tehkhunmag et al, 2008).…”
Section: Notementioning
confidence: 71%
See 1 more Smart Citation
“…Mehboob et al (2021) also found an increase in the water holding capacity of sorghum starch due to the introduction of hydroxypropyl groups into the starch structure. Increased water uptake percentage of different starches due to the hydroxypropylation process has been reported by different researchers (Karim et al, 2008;Park & Kim, 2020;Tehkhunmag et al, 2008).…”
Section: Notementioning
confidence: 71%
“…Hydroxypropylation (HP), which is a chemical modification method, reduces the hydroxyl group's number in the structure of starch and weakens the hydrogen bonds between the granules. Increasing the degree of hydroxypropylation can increase the freeze‐thaw stability, hydrophilicity, concentration, and clarity of paste (Fouladi & Mohammadi Nafchi, 2014 ; Park & Kim, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, low enthalpy demonstrates less stability of starch crystals and the structural order (Oh et al., 2019). Most studies on the modification of starch structures with hydroxypropylation process reported a decrease in the temperatures and enthalpy of gelatinization (Javadian et al., 2021; Mehboob et al., 2021; Oladebeye et al., 2019; Park & Kim, 2020; Shaikh et al., 2017; Wang & Shi, 2020). Tang et al.…”
Section: Resultsmentioning
confidence: 99%
“…However, at constant acid hydrolysis time, by increasing the propylene oxide ratio from 5% to 25%, the crystals and the structural order (Oh et al, 2019). Most studies on the modification of starch structures with hydroxypropylation process reported a decrease in the temperatures and enthalpy of gelatinization (Javadian et al, 2021;Mehboob et al, 2021;Oladebeye et al, 2019;Park & Kim, 2020;Shaikh et al, 2017;Wang & Shi, 2020). Tang et al (2012) also observed a decrease in gelatinization temperatures and enthalpy of acid-modified Kudzu root starch by hydroxypropylation process.…”
Section: The Pasting Propertiesmentioning
confidence: 99%